Auxiliar en supervisión de obra civil en Camargo construcciones y equipos S.A.S (2023)
This report is prepared to understand the development of the internship in the company Camargo Construcciones y Equipos S.A.S. Its objective is to support the supervision of work To solve the unforeseen events present in the works, it is necessary to have trained supervisors who control the activities to be carried out when a certain building is carried out, who have theoretical and practical knowledge to provide competent construction methodologies. Carry out the respective review of the designs, specification of materials and their quality, distribution of reinforcing steel, setting and curing times of concrete, execution process of a certain structural element according to technical details and other variables that influence proper functioning. of a structure are some of the items contemplated in the technical supervision of work as established in the current regulations that govern earthquake-resistant construction in our country and will be the topics of study in the development of this internship.